Volume-outcome relationship and minimum volume regulations in the German hospital sector: Evidence from nationwide administrative hospital data for the year 2005-2007 - Corinna Hentschker; Roman Mennicken; Antonius Reifferscheid; Jürgen Wasem; Ansgar Wübker (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This paper analyses the volume-outcome relationship and the effects of minimum volume regulations in the German hospital sector. We use a full sample of administrative data from the unselected, complete German hospital population for the years 2005 to 2007. We apply regression methods to analyze the association between volume and hospital quality. We measure hospital quality with a binary variable, which indicates whether the patient has died in hospital. Using simulation techniques we examine the impact of the minimum volume regulations on the accessibility of hospital services. We find a highly significant negative relationship between case volume and mortality for complex interventions at the pancreas and oesophagus as well as for knee replacement. For liver, kidney and stem cell transplantation as well as for CABG we could not find a strong association between volume and quality. Access to hospital care is only moderately affected by minimum volume regulations. The effectiveness of minimum volume regulations depends on the type of intervention. Depending on the type of intervention, quality gains can be expected at the cost of slightly decreased access to care. – – Dieser Beitrag analysiert den Zusammenhang zwischen der Zahl der Fälle eines Krankenhauses und der Ergebnisqualität sowie die Auswirkungen von Mindestmengenregelungen im deutschen Krankenhaussektor. Wir verwenden administrative Krankenhausdaten, die die vollständige deutsche Krankenhauspopulation für die Jahre 2005 bis 2007 enthalten. Dabei messen wir die Krankenhausqualität mit einer binären Variablen, die angibt, ob der Patient im Krankenhaus verstorben ist. Mit Hilfe von Simulationen untersuchen wir die Auswirkungen der Mindestmengenregelungen auf die Erreichbarkeit von Krankenhäusern. Wir finden signifikante negative Beziehungen zwischen Zahl der Fälle und Mortalität für die Indikationen komplexe Eingriffen an der Bauchspeicheldrüse und der Speiseröhre sowie bei Kniegelenkersatz. Bei Leber-, Nieren- und Stammzelltransplantationen sowie bei CABG konnten wir keinen starken Zusammenhang zwischen Zahl der Fälle und Qualität feststellen. Der Zugang zur Krankenhausversorgung wird insgesamt nur geringfügig von den Mindestmengenregelungen beeinflusst. Die Wirksamkeit der Mindestmengenregelungen hängt von der Art der Intervention ab. Je nach Art der Intervention sind Qualitätsgewinne zu erwarten, wenn der Zugang zur Versorgung etwas eingeschränkt wird.
Keywords: I12; I18; 330; Volume; hospital quality; mortality; access to care